Clara: An Actor Language for High Performance Distributed Computing - Duarte, Carlos H. C.; Talcott, Carolyn L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
In this paper we present Clara, a new programming language for high performance distributed computing. Clara has been developed to embody in an efficient distributed computing environment the conceptual clarity of the actor model, an object-based framework for the design and implementation of open distributed systems. We describe our Clara compiler, paying special attention not only to the adopted two stage translation process but also to the runtime environment, which is based on the message passing interface standard.